#41 Effect of Boswellia serrata in 3-NP induced experimental huntington disease - Sharma, Chanchal; Mishra, Tejesvi (Journal of Pharmaceutical Chemistry, 2022)
Huntington’s disease (HD), commonly known as Huntington’s chorea, is a hereditary neurodegenerative illness. Huntington’s disease is an autosomal dominant neurodegenerative condition marked by uncontrollable movements, cognitive impairment, and severe degradation of basal ganglia neurons in the neostriatum. Huntington’s disease (HD) causes cognitive and psychological disability due to neuronal degeneration in the brain. Several investigations have found that oxidative stress is the primary pathogenic component in HD. The current study seeks to assess the potential neuroprotective benefits of Boswellia serrata at three distinct oral dosages of 45 mg/kg, 90 mg/kg, and 180 mg/kg on 3-nitropropionic acid (3-NP)-induced HD. 3-nitropropionic acid (3-NP) is a toxin that inhibits the mitochondrial enzyme succinate dehydrogenase in the brain irreversibly. The 3-NP model is reliable for researching HD because it simulates a downstream pathway of cell death identified in the HD brain, especially mitochondrial dysfunction. In the current investigation, we used 3-NP at 10 mg/kg i.p. to induce HD in a rat model. This study looks at how effectively Boswellia serrata protects against HD. Boswellia species (Burseraceae) are widely utilized in herbal medicine across the world. Boswellia species, such as Boswellia serrata, produce oleo gum resin. Oleo gum resin can also be used to treat dysmenorrhea, gingivitis, wounds, ulcers, and as an anti-inflammatory agent. We will use 56 Wistar rats (8 per group) to assess biochemical and behavioral parameters. To our knowledge, this is the first study to look into the neuroprotective benefits of Boswellia serrata on 3-NP-induced HD.
Keywords: aaa